Sifat Fisik Tanah dan Laju Infiltrasi di Bawah Tegakan Gaharu (Aquilaria malaccensis) dan Ulin (Eusideroxylon zwageri) - Adelia Juli Kardika; Herijanto Thamrin; Agustina Murniyati; Rifki Noor Rosyid; Laode Muh Asdiq Hamsin Ramadan; Sakti AL’ Adiat Islami Putra (Fakultas Pertanian Universitas Almuslim Bireuen Aceh, 2026)
Forest ecosystems play an important role in regulating hydrological processes, particularly through soil physical properties that influence air infiltration and storage. This study aims to analyze and compare soil physical properties and infiltration rates under Aquilaria malaccensis (agarwood) and Eusideroxylon zwageri (ironwood) stands in the Samarinda State Agricultural Polytechnic campus area. Field infiltration measurements were conducted using a double ring infiltrometer, while soil physical properties analysis included soil texture, bulk density, particle density, porosity, air content, and organic carbon analyzed in the laboratory. The results showed that the soil in both stands was dominated by sandy texture. The soil under the agarwood stands had a composition of 85.08% sand, 6.59% silt, and 8.23% clay, while the soil under the ironwood stands consisted of 83.18% sand, 14.26% silt, and 2.56% clay. The soil bulk density under agarwood stands (1.70 g cm³) was higher than that under ironwood stands (1.39 g cm³). Conversely, soil porosity, water content, and organic carbon content were higher in ironwood stands, namely 46.12%, 28.7%, and 2.04%, respectively, compared to agarwood stands, which were 38.41%, 20.96%, and 1.69%, respectively. The constant infiltration rate under agarwood stands reached 12 cm min, while in ironwood stands it reached 18 cm min.